RANCANGAN APLIKASI PENGUKUR TINGKAT POLUSI UDARA BERBASIS ARDUINO UNO R3 DAN WEB - Sry Handayani; Atma Hadiansa; Masrizal Masrizal (STMIK Budi Darma, 2017)
Air pollution becomes an important issue that can threaten human life. Many human activities that cause air pollution. Therefore, an air pollution level monitoring is needed to determine the air pollution index in the area in order to maintain the pollutant level below its threshold value. With the Arduino Uno R3 Air Pollution Level Application and Website, it is possible to know the number of pollutant substances and also to get the necessary reports or information about the air condition and the anticipatory steps that can be taken to reduce the sensitive victim's unhealthy air